Recombinant Pichinde viral vector expressing tuberculosis antigens elicits strong T cell responses and protection in mice - Kirk, Natalie M.; Huang, Qinfeng; Vrba, Sophia; Rahman, Mizanur; Block, Alisha M.; Murphy, Hannah; White, Dylan W.; Namugenyi, Sarah B.; Ly, Hinh; Tischler, Anna D.; Liang, Yuying (Frontiers in Immunology, 2023)
Introduction Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) remains a major global health threat. The only available vaccine Bacille Calmette-Guérin (BCG) does not prevent adult pulmonary TB. New effective TB vaccines should aim to stimulate robust T cell responses in the lung mucosa to achieve high protective efficacy. We have previously developed a novel viral vaccine vector based on recombinant Pichinde virus (PICV), a non-pathogenic arenavirus with low seroprevalence in humans, and have demonstrated its efficacy to induce strong vaccine immunity with undetectable anti-vector neutralization activity. Methods Using this tri-segmented PICV vector (rP18tri), we have generated viral vectored TB vaccines (TBvac-1, TBvac-2, and TBvac-10) encoding several known TB immunogens (Ag85B, EsxH, and ESAT-6/EsxA). A P2A linker sequence was used to allow for the expression of two proteins from one open-reading-frame (ORF) on the viral RNA segments. The immunogenicity of TBvac-2 and TBvac-10 and the protective efficacy of TBvac-1 and TBvac-2 were evaluated in mice. Results Both viral vectored vaccines elicited strong antigen-specific CD4 and CD8 T cells through intramuscular (IM) and intranasal (IN) routes as evaluated by MHC-I and MHC-II tetramer analyses, respectively. The IN inoculation route helped to elicit strong lung T cell responses. The vaccine-induced antigen-specific CD4 T cells are functional, expressing multiple cytokines as detected by intracellular cytokine staining. Finally, immunization with TBvac-1 or TBvac-2, both expressing the same trivalent antigens (Ag85B, EsxH, ESAT6/EsxA), reduced Mtb lung tissue burden and dissemination in an aerosol challenge mouse model. Conclusions The novel PICV vector-based TB vaccine candidates can express more than two antigens via the use of P2A linker sequence and elicit strong systemic and lung T cell immunity with protective efficacy. Our study suggests the PICV vector as an attractive vaccine platform for the development of new and effective TB vaccine candidates.